The Effect of Flower Candle Aromatherapy on Postpartum Mother's Anxiety - Anggraini, Dina Dewi; Nurmalita Sari, Marlynda Happy (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Postpartum mothers experience psychological changes, one of which is anxiety. Lavender flower aromatherapy candles contain linalyl acetate and linalool which relax the mind and body. This study aims to determine the effect of giving flower candle aromatherapy on postpartum maternal anxiety. This research uses a quasi-experimental method with a pretest and posttest design model. The sampling technique is purposive sampling. The statistical tests used for pre and posttest in both groups used the dependent t-test (normal) or the Wilcoxon test (abnormal). And between control and treatment groups using the independent t-test (normal) or Mann-Whitney test (abnormal). The results of the research that has been carried out show that there is a difference in the anxiety of post-partum mothers who are given aromatherapy flower candles compared to postpartum mothers who are not given aromatherapy flower candles. The average anxiety in postpartum mothers who were given treatment or intervention (flower candle aromatherapy) was 0.77, while the average anxiety in post-partum mothers in the control group (psychological education) was 2.03. Likewise, the mean rank results show that postpartum mothers who were given treatment or intervention (flower candle aromatherapy) had a lower average anxiety, namely 20.77, than postpartum mothers in the control group (psychological education), namely 40.23.